The Adaptation Process of Rantau Students at Universitas Negeri Jakarta (UNJ) in Facing Culture Shock - Putri, Maulina Larasati; Sary, Marisa Puspita; Sutjipto, Vera Wijayanti; Putri, Amanda Kanary; Putri, Rizki Anindia (UMSU, 2024)
Culture shock is a condition experienced by a person when they feel afraid, anxious, and overly worried about the new environment they are facing. Students often experience culture shock, especially when they have to migrate outside their home areas to carry out their education. The purpose of this study is to find out how the adaptation process of overseas students of the Communication Studies study program at the State University of Jakarta in facing culture shock. The research method uses a descriptive qualitative approach where the informants of this research are seven overseas students of Communication Science UNJ class of 2020 who come from outside the island of Java, namely Medan, Riau, Tidore, Jambi, Padang, and Papua. The results obtained from this study are that overseas students experience a honeymoon phase, which is having a high curiosity and curiosity about the new atmosphere and environment they will live in, then they feel a phase of frustration which is the point of the culture shock phase, namely feeling unfamiliar and also frustrated. Then enter the third phase, which is readjustment where they begin to be able to accept and adapt to a new culture and environment. In the end, they go through a phase of resolution where they have a high sense of tolerance and try to make themselves comfortable with the new culture and environment.